A Feasibility Study of Debonding Detection in Multi-Layered Marine Thin-Wall Structures Using a Non-Destructive Vibration-Based Approach - Yona Dawit; Zima Beata; Krata Przemysław (Polish Maritime Research)
This study analyses different debonding defect scenarios on a multi-layered material composed of carbon fibre-reinforced polymer as a composite coating applied to structural steel, with the aim of applying it to marine structures. The study utilises vibration-based experimental non-destructive diagnostics and numerical simulations to thoroughly examine the debonding extent at four different lengths: 0%, 25%, 75%, and 100% of the total length of the material. The theoretical formulation of the free vibration of the proposed material for the fully bonded condition (0%) is also established using classical beam theory and the principles of composite materials. The four initial natural frequencies in the analysis provide indirect observations of the strength and stiffness properties. The results demonstrate that a reduction in the natural frequencies with increasing debonding size is mainly attributed to a loss of stiffness, rather than to the mass and stress distributions between the layers. Although debonding significantly affects the structure at longer lengths, only a small effect is observed when debonding covers 25% of the length. Based on the results, the experimental methods demonstrate strong agreement with the numerical approaches for determining natural frequencies, despite the unexpected results for the fundamental frequency of vibrations in the theoretical approaches. Eventually, we show that the prediction model established for this purpose accurately predicts the impact of debonding defects on the vibration characteristics of a structure with a high coefficient of determination.